339 Preliminary safety, tolerability and efficacy results of KN026 (a HER2-targeted Bispecific Antibody) in combination with KN046 (an anti-PD-L1/CTLA-4 Bispecific Antibody) in patients (pts) with HER2 aberrated solid tumors. (9th November 2020) - Gong, Jifang; Dong, Zhi; Liu, Dan; Xu, June; Yang, Jing; Yang, Yue; Qi, Yakun; Men, Jie; Kong, Paul; Xu, Ting; Shen, Lin
Abstract : Background: HER2 potently inhibits innate immunity through cGAS–STING signalling, 1 meanwhile HER2 antibody induced ADCP will also lead to macrophage mediated immune suppression. Preclinical and clinical studies suggested a coordination of engagement of innate and adaptive immunity with the combination of an anti-HER2 antibody and an immune checkpoint blockade. KN026 is a novel bispecific antibody that simultaneously binds to two distinct HER2 epitopes. KN046 is a novel bispecific antibody that blocks both PD-L1 interaction with PD-1 and CTLA-4 interaction with CD80/CD86. Here we reported the interim results from an ongoing phase Ib dose escalation and expansion study assessing the safety, tolerability and preliminary efficacy for KN026 in combination with KN046. Methods: This study enrolled pts with solid tumors who failed available standard of care, HER2 aberration status confirmed locally (HER2 mutation, HER2 amplification and/or HER2 overexpression). Eligible pts received combination of KN026 and KN046 at two dose levels until disease progression, unacceptable toxicity or withdrawal of informed consent (DL1: KN026 20 mg/kg Q2W + KN046 3 mg/kg Q2W; DL2: KN026 20 mg/kg Q2W with loading on Days 1, 8 of Cycle 1 + KN046 5 mg/kg Q3W). Tumor response was evaluated Q8W per RECIST 1.1. Primary endpoint was DLT and key secondary endpoints were efficacy parameters (ORR, DOR, PFS). Results: As of the Jul. 13, 2020, 21 pts were enrolled into DL1 (n = 18, 3 for dose escalation) and DL2 (n = 3) (mGC/GEJ 12 pts; mCRC 7 pts; other solid tumors 2 pts). 11 pts remained on the study treatment and 10 pts discontinued treatment due to disease progression (n=5), death (n=2) and other reasons (n=3). 15 pts had HER2-positive status (11 of 15 failed previous trastuzumab therapy), 1 pts had HER2 mutation and 5 pts had HER2 low expression (without FISH amplification). No DLTs were observed. No pts experienced LVEF decreased or other clinically meaningful cardiac AEs. Treatment-related TEAEs occurred in 13 pts, of which 1 pts experienced grade 3 or above treatment-related TEAEs. 7 pts experienced irAEs, all of which were grade 1 or 2. The most common (≥ 10%) KN026 or KN046 related TEAEs were anaemia (n=5, 23.8%), AST increased (n=4, 19.0%), rash (n=4, 19.0%), diarrhea (n=4, 19.0%), blood bilirubin increased (n=3, 14.3%) and infusion related reaction (n=3, 14.3%). The objective response rate in pts with HER2-positive tumors (n = 7 efficacy evaluable pts) was 4/7 (57.1%, 95% CI 18.4 90.1%) and disease control rate 6/7 (85.7%, 95% CI 42.1 99.6%). 3 pts with HER2 mutation or low expression achieved SD including one patient with SD for more than 24 weeks. 2 death cases only received one cycle of KN026 plus KN046 due to COVID-19 restriction before died from clinical deterioration from underlying tumors. Conclusions: KN026 combined with KN046 is well tolerated and has demonstrated profound anti-tumor activity in HER2-positive solid tumors. Trial Registration: NCT04040699 Ethics Approval: The study was approved by Beijing Cancer Hospital Institution's Ethics Board, approval number 2019YJZ37. Consent: Written informed consent was obtained from the patient for publication of this abstract and any accompanying images. A copy of the written consent is available for review by the Editor of this journal. Reference: Shiying Wu, Qian Zhang, Fei Zhang, et al. HER2 recruits AKT1 to disrupt STING signalling and suppress antiviral defence and antitumour immunity. Nature Cell Biology 2019;21: 1027–1040.